Roosting and nesting ecology of house sparrow (\(Passer domesticus\)) in Guwahati city, Assam - Pegu, Snigdha; Nag, Sudipta; Hasan, Rubaiya; Das, Arup Nama (Academia Journal of Biology, 2024)
Aves are unique in having a coat of feathers and in balancing on the hind limbs alone. They are known as the feathered bipeds. Roosting, nest building in birds has been considered a remarkable behaviour in aves. The nesting ecology of birds is likely the most important component of its life history and it is affected by several ecological and environmental factors. Guwahati city, a rapidly growing city in northeast India inhabits a lot of species of birds. It is located between the Brahmaputra River’s southern bank and the Shillong plateau’s foothills. Total of the 57 nests, 28% were discovered in the rolling shop shutters, followed by 27% in the tin sheet roofs of homes, followed by 19% in building crevices, 9% in building holes, 7% in advertisement hoarding and 5% in AC outdoor units and 5% in unused building pipes. It is also observed that 49% of the nests are located at a height between 2–4 metres from the ground level, 70% of the nests are located between 1–5 metres from the nearest food source, and 58% of the nests are located between 1–5 metres from the nearest water source. Out of the 57 nests observed, 50 were found to be solitary, 5 were found to be Pair, and 2 were found to be cluster type. The study found that choosing a nest is influenced directly by the location of the nearest food source and nearest water source in Guwahati city. The study presents the merit and needs for studying the nesting ecology of birds in India, also suggests best practices to conserve bird’s nest specific to the Indian context which might provide important information for the nesting ecology of House Sparrows (Passer domesticus).